Women's International League for Peace and Freedom, 1919 (1919)
1919 1918-1939 "Women's International League for Peace and Freedom, 1919" [EP0212], 1919 Photograph of the British delegation to the 1919 Zurich Congress of the Women's International League for Peace and Freedom. Included are Margaret Ashton, Harriet Briggs, K. D. Courtney, Mrs Crawford, Charlotte Despard, Gertrude Eaton, Mrs Anderson Fenn, Miss I O Ford, Mrs Giles, Miss Hardcastle, Huth Jackson, Mrs Pethick Lawrence, E.M Leaf, Chrystal Macmillan, E. Macnaghten, Catherine Marshall, Annot Robinson, Miss Royds, Mrs Rollo Russell, A. Salter, M. Sheepshanks, Mrs Philip Snowden, Mrs Swanwick, Ellen Wilkinson, Dr Ethel Williams and T. Wilson. The Congress urged the Peace Conference then meeting in Paris to include a Women's Charter in the final Peace Treaty. The 12 point Charter included equal suffrage, equal pay and opportunities in employment and education, and economic support for mothers.